2021
DOI: 10.2174/1574886315999201208212356
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Cardiovascular Safety of GLP-1 Receptor Analogues

Abstract: Abstract:: Glucagon like peptide- 1 receptor analogs (GLP-1RAs) are incretin mimetics with potent glucose-dependent insulinotropic action that translates to glycemic control in people with type-2 diabetes mellitus (T2DM). These agents potentially have the ability to stimulate proliferation or prevent apoptosis of pancreatic β-cells, induce weight-loss and provide vascular benefits in patients with T2DM. Newer GLP-1RA, semaglutide has shown robust reduction in HbA1c up to 1.5 - 1.8%. However individual differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Compared with people of the same age and gender, children and adolescents with higher BMI levels may have multiple cardiovascular risk factors ( 23 ). It has been demonstrated that different types of GLP-1RAs have individual differences in efficacy and vascular protection ( 24 ). For instance, liraglutide has been proven to lower the risk of major adverse cardiovascular events (MACE), while lixisenatide and slow-release exenatide had a neutral effect ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with people of the same age and gender, children and adolescents with higher BMI levels may have multiple cardiovascular risk factors ( 23 ). It has been demonstrated that different types of GLP-1RAs have individual differences in efficacy and vascular protection ( 24 ). For instance, liraglutide has been proven to lower the risk of major adverse cardiovascular events (MACE), while lixisenatide and slow-release exenatide had a neutral effect ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…After the approval of exenatide for the management of T2DM in 2005, several molecules of GLP-1RAs were introduced into the global drug market, and newer agents are currently under development. Iqbal et al in this issue of the Journal, have provided us a concise and critical review titled “Efficacy and cardiovascular safety of GLP-1 receptor analogues” that analyses the biopharmaceutical properties, efficacy, and cardiovascular safety issues surrounding the use of GLP-1RAs [ 46 ]. Based on the evidence from multiple large RCTs and meta-analyses, the authors have concluded that the use of GLP-1RAs is associated with HbA1c reduction of up to 1.8%, depending on the baseline HbA1c and baseline body weight/ diabesity.…”
mentioning
confidence: 99%
“…Iqbal et al have also elaborated the cardiovascular benefits associated with GLP-1RAs based on the extensive review of the 6 CVOTs using various molecules belonging to this drug class, such as lixisenatide liraglutide, exenatide, dulaglutide, and semaglutide [ 46 , 47 ]. CVOTs showed mortality reduction with only liraglutide and possibly semaglutide, the other three agents in the class did not show this benefit.…”
mentioning
confidence: 99%